(untitled) (Revista Educação, Artes e Inclusão, 2020)
The reflections that follow here dialogue with the post-doctoral research carried out at the Center for the History of Art and Artistic Research (CHAIA), which sought to deepen the idea that the intentional use of different materialities in the paths of theatrical creation mobilizes those involved helping to react to the established experiences, facilitating the interaction between the participants. The article is divided into two central parts: the first contains a presentation of an excerpt of the teaching experience lived with the students of the Basic Education Degree course at the University of Évora, in the discipline Workshop on Integration of Expressions; and the second is dedicated to issues raised by the theatrical work developed with children, in the context of basic education 1st cycle at Escola da Cruz da Picada. The multiple possibilities offered by the materialities at play in the two contexts, open perspectives to participants thinking and doing, to be more inventive and sensitive. As the learning process passes through your body and the other’s body, it allows you to experience new forms of community, conceiving alterity in a broader way. The results obtained are aimed at improving the training of teachers and researchers in theater pedagogy in the Brazilian and Portuguese context, building new collaborations.